An Empirical Analysis of Tamil Optical Character Recognition - Radhika, B. (Journal of Innovative Image Processing, 2022)
The concept of visual cues in a paperless workspace is based on converting scanned images into machine-readable text. It requires the development of a variety of new applications, such as automated postal systems, banks, institutions, word processing, and library systems, to name a few. Artificial Intelligence (AI) is an area of computer science that focuses on making machines smart. Hand typing, script, and print text recognition are key study subjects because no 100% recognition can be achieved even if the scanned image is accurate. Text, numbers, and images can all be used to write text in a variety of ways. The basics of Tamil text, previous tasks in Tamil text attention, Tamil letter recognition algorithms, and recognition barriers are covered in this study.
Keywords: Artificial intelligence; optical character recognition; tamil language; tamil script; visual cues